Association between estimated pulse wave velocity and stroke in middle-aged and elderly Chinese: A nationwide cohort study - Xiaomei Zheng; Yixian Zhang; Pengsheng Chen; Shengren Xiong (PLoS ONE, 2025)
Background Research on the relationship between estimated pulse wave velocity (ePWV) and stroke risk remains limited. Therefore, this study aimed to investigate the association between ePWV and the risk of stroke in middle-aged and older adults in China. Methods This cohort study included 9,190 participants from the China Health and Retirement Longitudinal Study (CHARLS) in 2011, with follow-up assessments in 2013, 2015, and 2018. ePWV values were categorized into tertiles. Stroke was defined as the occurrence of stroke during follow-up. Longitudinal associations between ePWV and stroke risk were evaluated using Cox proportional hazards regression models. Results In the fully adjusted model, compared to the first tertile, both the second and third tertiles were significantly associated with an increased risk of stroke, with a 40% higher risk for the second tertile (HR = 1.40, 95% CI: 1.17–1.76, P = 0.004) and a 42% higher risk for the third tertile (HR = 1.42, 95% CI: 1.08–1.86, P = 0.012). Restrictive cubic spline analysis further demonstrated a nonlinear dose-response relationship between ePWV and stroke risk (P nonlinear = 0.001). Conclusions Our findings suggest that elevated ePWV is significantly associated with an increased risk of stroke in middle-aged and elderly Chinese individuals. ePWV can screen individuals at high risk of stroke early in clinical practice and guide personalized prevention and intervention strategies.